Is greater generic competition also linked to lower drug prices in South Korea? - Kyung-Bok Son (Health Economics Review, 2020)
Background: Although the association between the price of generic drugs and market competitiveness has been explored in various high-income countries, this association has not been empirically evaluated in South Korea. We aim to determine the association between the prices of generic drugs and market competitiveness in South Korea. Methods: A list of originator drugs approved by the national authority from 2000 to 2019 and their corresponding generic drugs were grouped along with the baseline information. The market was categorized into four groups based on the number of manufacturers: duopoly (2 manufacturers); low- (3-25 manufacturers); medium- (26-75 manufacturers); and high-competition (more than 76 manufacturers) markets. Price variance, calculated as the difference between the maximum price and minimum price divided by the maximum price, was obtained. A multivariate regression model was applied to regress price variance on the characteristics of market competitiveness, controlling for the characteristics of the originator drugs and their price level in the market. Results: A total of 986 originator drugs were identified and then divided into duopoly (31%), low- (56%), medium- (9%), and high-competition (4%) markets; the median of the price variance for these markets was 0.013, 0.077, 0.200, and 0.228, respectively. In a multivariate regression model, price variance was associated with the characteristics of the originator drug, including the Anatomical Therapeutic Chemical classification, the route of administration, and the approval year. Controlling for the characteristics of the originator drugs, market competitiveness was positively associated with price variance. Conclusions: The positive association between price variance and market competitiveness is still consistent in South Korea, where rare price competition among a large number of generic manufacturers has been reported. However, no significant price variance was observed between medium- and high-competition markets. These findings support policies for managing a large number of generic manufacturers in South Korea.
Keywords: 330; Generics; Competition; Drug price; Market; South Korea